Interspecific Phylogenic Relationships within Genus Melilotus Based on Nuclear and Chloroplast DNA - Di, Hongyan; Duan, Zhen; Luo, Kai; Zhang, Daiyu; Wu, Fan; Zhang, Jiyu; Liu, Wenxian; Wang, Yanrong (PLOS ONE, 2015)
Melilotus comprises 19 species, while the phylogenetic relationships between species remain unclear. In the present work, three chloroplast genes, rbcL, matK, trnL-F, and one nuclear region, ITS (internal transcribed spacer) belonging to 48 populations of 18 species of Melilotus were sequenced and phylogenetic trees were constructed to study their interspecific relationships. Based on the phylogenetic tree generated in this study using rbcL analysis, the Melilotus genus is clearly monophyletic in the legume family. Both Bayesian and maximum-parsimony approaches were used to analyze the data. The nrDNA ITS provided more informative characteristics (9.8%) than cpDNA (3.0%). Melilotus contains two closely related groups, clade I and clade II. M. spicatus, M. indicus and M. segetalis have a close relationship. M. infestus, M. siculus and M. sulcatus are closely related. The comparing between molecular phylogeny and flower color classification in Melilotus showed that the flower color is not much informative for phylogenetics of this genus.